Public Pension Plans: Standards of Design, Funding, and Reporting. - Burns, Thomas J.; Hicks, Ernest L. (The Accounting Review, 1981)
Reviews the book "Public Pension Plans: Standards of Design, Funding, and Reporting," by Howard E. Winklevoss and Dan M. McGill.